Administración Pública Y Su Incidencia En La Ejecución De Proyectos Sociales Participativos De La Dirección De Desarrollo Social Del Gad Quevedo, Año 2023 - Coello Guerra, Maritza Amparo (2025)
ABSTRACT This research entitled Public Administration and its impact on the execution of participatory social projects of the Social Development Directorate of the GAD Quevedo year 2023, is justified by its importance within the current framework of Public Administration, at a time when administrative efficiency and citizen involvement have become essential elements for effective government, the objective is to evaluate public administration and its impact on the execution of social projects, this research is of a mixed type, that is, qualitative-quantitative because surveys and statistical and qualitative analysis such as views and participant observation were used as instruments, to understand the perceptions and experiences of project participants. A sample of 314 beneficiaries was taken as a reference, where as a result it was found that around a third are unaware that social projects are managed through the GAD of Quevedo, they consider that there is no good promotion, they estimate that there is a lack of socialization in their communities, among the conclusions we have that controls, supervision, transparency and evaluation of said participatory social projects should be intensified. Effective management is recommended, combining appropriate planning, adequate resource allocation, and the implementation of clear and inclusive participation strategies to increase the efficiency and sustainability of these resources.